Intellectual Capital, Arus Kas Operasi, Dan Nilai Perusahaan: Investigasi Pengaruhnya Terhadap Kinerja Perusahaan Manufaktur DiIndonesia - Waskito, Shiddiq; Effendy, Lukman (SAFE-Network, 2025)
A study was conducted to investigate the effects of intellectual capital, operating cash flow, and firm value on the performance of manufacturing companies in Indonesia. The manufacturing sector faces challenges such as intense competition, changing consumer preferences, and environmental regulations. This study employed a descriptive quantitative method, utilizing manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. A total of 143 companies were included as research samples. The findings indicate no crucial relationship between intellectual capital and company performance. However, operating cash flow and firm value were found to positively and crucially influence the financial performance of manufacturing companies. This suggests that healthy cash flow management and positive market perception of firm value are important factors in achieving strong financial performance within the manufacturing sector.